THE PROBLEMATICS OF LAW ENFORCEMENT AGAINST THE EXECUTION OF ELECTORAL PENALTIES IN INDONESIA - Lubis, Andi Hakim; Siagian, Fahrizal S.; Putra, Panca Sarjana; Firouzfar, Saied (Fakultas Hukum, Universitas Semarang, 2024)
Crimes occur in many ways, one of them in the context of elections in Indonesia. The potential crimes perpetrated by political party supporters in various areas of Indonesia whose law enforcement is not working to the maximum is one of the problems. The problem in this study is first, how do legal provisions relate to law enforcement against electoral crimes in Indonesia? Secondly, the problem of law enforcement against electoral crimes in Indonesia? Third, reconstruction of law enforcement against electoral crimes in Indonesia? The aim of this research is to determine the regulation and legal analysis of the forms of crime black campaigns in accordance with the law. This research uses normative law research with secondary data and processes data from primary, secondary, and tertiary legal materials. The results of the first study are that the legal provisions for electoral offences in Indonesia are regulated in the Law Number 7 of 2017, Criminal Law, and the Law on Electronic Information and Transactions. (ITE). Second, that the Law Enforcement Problems Against Electoral Crimes in Indonesia, i.e. the inadequate application of criminal law in elections, constitutes an obstacle to the increase in the incidence of electoral crimes that have violated the Election Law Number 7 of 2017 and the Penal Code as well as the Information and Electronic Transaction Law. (ITE). Thirdly, it is expected that Indonesia will have a specialized agency that will strictly prosecute electoral criminals. Therefore, it can be concluded that electoral crimes are not maximized due to weak enforcement of electoral law.